Institutional Quality and Economic Growth in the Energy Transition of MENA Countries - Mtiraoui, Abderraouf; Lazreg, Marwa; Chemli, Leila (International Journal of Energy Economics and Policy, 2024)
This paper investigates the energy transition in MENA region countries, emphasizing the pivotal role of institutional quality and its impact on economic growth. It explores the interactions between institutional quality, energy transition initiatives, and economic growth, aiming to understand how strong institutions can facilitate a successful transition. The empirical analysis employs a simultaneous equations model to identify institutional factors that can either support or hinder the energy transition and its influence on economic growth. The findings provide valuable insights for policymakers and economic stakeholders, underscoring the critical importance of robust institutions in driving the energy transition process and stimulating economic growth in the MENA region from 2000 to 2022.